The U.S. Current Account and Real Effective Dollar Exchange Rates - Joscha Beckmann; Ansgar Belke; Robert Czudaj (Credit and Capital Markets – Kredit und Kapital, 2013)
This study analyzes long-run and short-run dynamics between the current account and the real effective dollar exchange rates from a novel perspective. Applying multivariate cointegration techniques, we first test for a long-run relationship between the real effective dollar exchange rate and the U.S. current account. We then include further macroeconomic factors as an extension. As a next step, we pay particular attention to the evolvement of the coefficients over time based on an estimation of a time varying coefficient approach by means of Kalman filtering. (E31, F31) – – Die US-Leistungsbilanz und reale effektive Dollar-Wechselkurse Diese Studie analysiert die lang- und kurzfristige Dynamik zwischen der USamerikanischen Leistungsbilanz und realen effektiven Dollar-Wechselkursen auf innovative Weise. Im Rahmen einer Anwendung multivariater Kointegrationstechniken testen wir zunächst auf das Vorhandensein einer langfristigen Gleichgewichtsbeziehung zwischen dem realen effektiven Dollar-Wechselkurs und der USLeistungsbilanz. Als Erweiterung nehmen wir weitere makroökonomische Variablen in den Ansatz auf. Schließlich analysieren wir unter Verwendung eines zeitvariierenden Koeffizienten-Ansatzes und eines Kalman-Filters die zeitliche Entwicklung der Koeffizientenschätzer. (E31, F31)
Keywords: 330